reward is 15 points for answering
Attachments:
![](https://hi-static.z-dn.net/files/db5/375bcf5e17bc25485dd415dc1b638a00.jpg)
Answers
Answered by
2
this is the full answer Hope it helps
Attachments:
![](https://hi-static.z-dn.net/files/de4/f09ebfdb038c1449485c3b56bf0b927c.jpg)
aribaparveen:
thanks
Answered by
0
Answer:
Let : x = 5 + 2√6.
Then : x = 3 + 2 + 2√((3)(2))
∴ x = (√3)² + (√2)² + 2(√3)(√2) = (√3 + √2)²
∴ √x = √3 + √2 ................................................ (1)
∴ 1/(√x) = 1/(√3 + √2) = √3 - √2 ....................... (2)
∴ (√x) + (1/√x) = 2√3.................................................... Ans,
_______________________________
Happy To Help !
_______________________________
10
Step-by-step explanation: brainliest pls.
Similar questions
Biology,
7 months ago